Evaluation of Breast Vascular Calcifications as a Predictor for Coronary Artery Calcification - D. A. Bazhenova; O. S. Puchkova; E. A. Mershina; V. E. Sinitsyn (Вестник рентгенологии и радиологии)
Background. Cardiovascular diseases are one of the main causes of death among women, and current prevention paradigms may not be sufficient in this group. In this context, it has been suggested that the detection of breast vascular calcifications can improve the screening and assessment of the risk of cardiovascular diseases in apparently healthy women.Objective: to study the role of breast vascular calcifications as a potential predictor for coronary artery calcification. Material and methods. Examinations were made in 123 patients who underwent digital mammography and cardiac computed tomography to estimate a coronary artery calcium score.Results. The use of the Wilcoxon-Mann-Whitney W-test for abnormal distribution showed a relationship between the presence of breast vascular calcifications and calcium score (p< 0.001), and that between aortic wall calcification and calcium score (p< 0.001).Conclusion. Breast vascular calcifications detected by mammography are an indicator of a higher frequency of coronary artery calcification and, apparently, a predictor for the increased risk of cardiovascular disease.